O movimento ensina a gente a falar, a se posicionar e a não ter vergonha da nossa identidade": percepções de jovens Karipuna sobre o processo educativo no movimento indígena - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2026)
The dissertation analyzes the perceptions and meanings attributed to the educational process by Karipuna Indigenous youth from the Santa Izabel village, located in the municipality of Oiapoque, Amapá, within the context of their participation in the Indigenous movement. The central objective was to understand how these educational experiences, both formal and non formal, contribute to the identity, political, and cultural construction of these subjects. The research adopted a qualitative approach, grounded in narrative research and participant observation, with the locus being the Santa Izabel village in the Uaçá Indigenous Land, involving young community leaders as participants. The data show that the educational process goes beyond the limits of formal schooling, incorporating traditional knowledge, the mother tongue, community practices, and teachings transmitted by elders—elements that are fundamental for the formation of subjects aware of their ancestry and committed to collective struggles. It was found that, although the school located in the Indigenous territory still reproduces, to some extent, a Eurocentric logic, the Indigenous movement constitutes a formative space of resistance, identity strengthening, and political articulation, fostering the appreciation of traditional knowledge and the demand for an intercultural, specific, and differentiated education. The analyses reveal tensions between Western knowledge and Indigenous knowledge, as well as the relevance of youth protagonism in the continuity of struggles for territorial, cultural, and educational rights. It is concluded that the Indigenous movement plays an essential role as an expanded educational territory in which meaningful learning is produced for autonomy, identity affirmation, and the cultural resistance of the Karipuna people in the face of contemporary challenges.
“Muvmã dji ēdjē ka mõthe no koze, gãiē un pozisiõ i pa hõte dji no idãtxite”: viziõ dji jon-mun-iela Karipun suje phose dji edukasiõ lãdã muvmã dji ēdjē
Keywords: Educação Indígena; Indígenas da América do Sul - Educação – Brasil; Povos Indígenas - Karipuna - Brasil; CNPQ::CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; ODS 4 – Educação de qualidade; ODS 10 – Redução das desigualdades; ODS 16 – Paz, justiça e instituições eficazes